Do Multinationals Pay Less in Taxes than Domestic Firms? Evidence from the Swedish Manufacturing Sector - Åsa Hansson; Karin Olofsdotter; Susanna Thede (Lund University, School of Economics and Management, Department of Economics, 2016)
There is a strong general concern amongst policymakers worldwide that multinational enterprises engage in far-reaching tax-planning activities. It is generally thought that by using transfer pricing or other techniques to shift profits, multinational enterprises can avoid taxation and thereby erode tax bases. Several attempts have been made to tackle this problem, not least through the OECD/G20 initiated Action Plan on Base Erosion and Profit Shifting. It is hard, however, to empirically quantify the magnitude of tax-planning activities that takes place. In this paper, we rely on census data from tax return and income statements and balance sheets reported by Swedish manufacturing firms in the 1997-2007 time period to identify possible profit-shifting activities by multinational enterprises. We study systematic differences between multinational and comparable domestic firms in tax payments, profits, earnings before interest and taxes, and equity ratios using difference-in-differences estimations based on propensity score matching. The detailed data allow us to narrow down the empirical focus and investigate not only whether multinational pay less in taxes than domestic firms, but also how tax planning activities may take place through transfer pricing and/or internal debt set-ups.
Keywords: F23; H26; L20; 330; Firm behavior; Tax planning; Profit shifting